2000
DOI: 10.1002/(sici)1097-0223(200002)20:2<91::aid-pd759>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for trisomy 21 in twin pregnancies in the first trimester using free ?-hCG and PAPP-A, combined with fetal nuchal translucency thickness

Abstract: In the first trimester of pregnancy the biochemical markers free beta-hCG and pregnancy associated plasma protein-A (PAPP-A) are used for the prenatal screening of trisomy 21, either alone or in combination with nuchal translucency (NT) thickness. In this study, I have analysed the distribution of these biochemical markers in 159 twin pregnancies and compared this with 3466 singleton pregnancies. On average free beta-hCG values are 2.099 times greater in twins than in singletons and PAPP-A some 1.86 times grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
65
0
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 16 publications
10
65
0
9
Order By: Relevance
“…The median MoM PAPP-A after weight correction and before correction for twin pregnancy was 1.93 with a mean log 10 of 0.2628 and a log 10 standard deviation of 0.2178. These values are very similar to those published in a previous series 9 .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The median MoM PAPP-A after weight correction and before correction for twin pregnancy was 1.93 with a mean log 10 of 0.2628 and a log 10 standard deviation of 0.2178. These values are very similar to those published in a previous series 9 .…”
Section: Resultssupporting
confidence: 91%
“…Using a 'pseudo risk' approach, combining fetal nuchal translucency thickness and maternal serum biochemistry was predicted to identify 80% of cases of twins discordant for trisomy 21 (at a 5% false positive rate) and 81.5% in concordant twins. Thus, it was argued that while maternal serum biochemistry alone could not specifically identify the fetus at risk in the presence of twins discordant for trisomy 21, it would be possible to enhance the detection rate in twins by some 5 -6% yet still retain the benefits of nuchal translucency thickness in identifying the specific affected twin 9 . Furthermore, it has been shown that chorionicity has no impact on the maternal serum biochemical marker levels in twin pregnancy 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In twin pregnancies, both NT and maternal serum biochemistry can be combined (Spencer, 2000) to provide detection rates that would approach those achieved in singleton pregnancies. Whilst these early algorithms were based on relatively small numbers of cases of twins, retrospective use has shown them to be useful in identifying pregnancies discordant for trisomy 21 Nicolaides, 2000, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…A higher screen-positive rate and a lower detection rate compared with that in singleton pregnancies was reported in a Caucasian population 15 . The higher screen-positive rate is secondary to a higher prevalence of increased NT in twin fetuses, especially among monochorionic twins 16 . The two first-trimester biochemical markers only add a further 5% to the detection rate compared with using NT alone.…”
Section: Discussionmentioning
confidence: 99%